The Relevance of E-Learning in Higher Education - Wani, Hilal Ahmad (ATIKAN, 2013)
ABSTRACT: E-learning is a technology which supports teaching and learning via a computer and the web technology. It bridges the gap between a teacher and a student in two different geographical locations. Advancement in internet and multimedia technology is the basic enable for e-learning. E-learning applications facilitate online access to learning content and administration. Despite much enthusiasm about the roles of technology in education, its role in transforming teacher learning, in ways aligned with advances in the learning sciences and contemporary socio-cultural perspectives, few changes have occurred. While many teacher educators are turning away from technology, after early attempts met with mitigated success, some are pushing the boundaries of teacher education and professional activity systems. This paper identifies and analyzes emerging trends and models in e-learning for teacher education and professional development from the developing research base, both international trends and current developments. Educational institutions and teaching staff have many benefits due to emergence of modern technology. Teachers have their own networks through which they connect themselves with other teachers across the globe. Institutions have web-supported classrooms. Similarly, it also enhanced the responsibilities of schools, colleges, and universities that should have such teachers who can produce such students, who after receiving their education can adjust themselves at any platform.KEY WORD: E-learning, higher education, multimedia technology, teaching and learning, networks, online access, and professional development.IKHTISAR: Artikel ini berjudul âRelevansi E-Learning di Perguruan Tinggiâ. E-learning adalah teknologi yang mendukung pengajaran dan pembelajaran melalui komputer dan teknologi web. Ia menjembatani kesenjangan antara guru dan siswa di dua lokasi geografis yang berbeda. Kemajuan internet dan teknologi multimedia adalah kemampuan mendasar untuk e-learning. Aplikasi e-learning memfasilitasi akses online untuk konten dan administrasi pembelajaran. Meskipun banyak antusiasme tentang peran teknologi dalam pendidikan, perannya dalam mengubah pembelajaran guru, dengan menyelaraskan kemajuan ilmu pembelajaran dengan perspektif sosial-budaya kontemporer, masih sedikit perubahan telah terjadi. Sementara banyak pendidik guru yang berpaling dari teknologi, setelah upaya awal menemui kekurang-berhasilan, ada pula yang mendorong mengatasi batas-batas pendidikan guru dan sistem kegiatan profesional. Makalah ini mengidentifikasi dan menganalisis tren dan model dalam e-learning untuk pendidikan guru dan pengembangan profesional dari penelitian dasar dan pengembangan, baik secara tren internasional maupun perkembangan saat ini. Lembaga pendidikan dan staf pengajar memiliki banyak manfaat karena munculnya teknologi modern ini. Paru guru memiliki jaringan mereka sendiri di mana mereka dapat menghubungkan diri dengan guru-guru lain di seluruh dunia. Lembaga-lembaga memiliki ruang kelas berbasis web yang mendukung. Demikian pula, ianya meningkatkan tanggung jawab sekolah, perguruan tinggi, dan universitas yang harus memiliki guru-guru yang dapat menghasilkan para siswa, setelah menerima pendidikan, mereka dapat menyesuaikan diri dengan program apapun.KATA KUNCI: E-learning, perguruan tinggi, teknologi multimedia, pengajaran dan pembelajaran, jaringan, akses online, dan pengembangan profesional.About the Author: Dr. Hilal Ahmad Wani is a Research Fellow at the Centre for Civilizational Dialogue UM (University of Malaya) in Kuala Lumpur, Malaysia. For academic purposes, the author is able to be contacted via his e-mail address at: wanihilal@gmail.comHow to cite this article? Wani, Hilal Ahmad. (2013). âThe Relevance of E-Learning in Higher Educationâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.3(2) December, pp.181-194. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung and FKIP UNSUR in Cianjur, West Java, ISSN 2088-1290. Chronicle of the article: Accepted (October 1, 2013); Revised (November 2, 2013); and Published (December 15, 2013).